Digitalization Marketing and Payments for Sustainable Business at PT Albilad Internasional Group - Pebrianti, Yulia; Yogasnumurti, Raras Risia; Yuvita, Heni; Firdaus, Muhammad Ilham; Harmawansyah, Theo; Zulfani, Zulfani (Penerbit Goodwood, 2026)
Purpose: This study aims to formulate strategic steps to optimize the use of digital technology in supporting the business sustainability of PT Albilad Internasional Group, a provider of Umrah and Hajj travel services in Palembang. Research Methodology: This research employed a qualitative approach conducted at PT Albilad Internasional Group. Data were collected through in-depth interviews, direct observations, and document analyses. The data were analyzed using descriptive qualitative techniques to explore the contextual challenges and opportunities related to digital transformation. Results: The findings indicate that PT Albilad Internasional Group has begun adopting digital innovations, such as social media for marketing activities and Quick Response Code Indonesian Standard (QRIS) for non-cash payments. However, its implementation remains suboptimal due to the absence of a structured digital strategy and limited customer adoption of digital systems. This study proposes several strategic recommendations, including strengthening social media management, enhancing digital communication strategies, and increasing customer engagement with digital payment services. Conclusions: The study concludes that although PT Albilad Internasional Group has gradually integrated digital marketing and payment technologies, further optimization is necessary to enhance competitiveness and ensure long-term business sustainability in an increasingly digitalized travel industry. Limitations: This study focused on a single company and utilized a qualitative design, which may limit the generalizability of the findings. Contributions: This study contributes to the academic literature and provides practical insights for travel agencies seeking to improve their digital marketing and payment systems.